Histological and histochemical studies in ductus deferens of camel: Non-glandular part - GOSWAMI, S K; SINGH, YASHWANT; NAGPAL, S K (The Indian Journal of Animal Sciences, 2013)
The ductus deferens was characterized by folded mucosa lined with pseudostratified ciliated epithelium in scrotal, inguinal and abdominal regions, The propria-submucosa was thin, The tunica muscularis Was made up of 2 layers of smooth muscle fibres in all the 3 regions. A moderate PAS activity was observed insupranuclear zone and stereocilia in scrotal and abdominal regions which decreased slightly in inguinal region, The basal cells contained large lipid globules. Tim supranuclear zone of scrotal and inguinal regions showed intense alkaline phosphatase activity. A strong acid phosphatase activity was seen in the epithelium lining the duct in all the 3 regions.